9. The Critical Role of Art Education in Community Building as Viewed by Art Teachers. A Qualitative Study - Assante Gabriela Monica; Enescu Florin (Sciendo, 2020)
The present study aims to describe the ways in which art education impacts community life through art products. The sample consists of 32 teachers/creators in various fields of work such as fine arts, composition, literature, musical interpretation, choreography and acting. Categorical content analysis is used for data analysis. The highest-ranking emerging theme is related to the means of educational intervention in the community through art. Artistic education leads to empowerment and emancipation by provoking people to think differently while the exposure to artistic creations has a therapeutic effect and contributes to identifying new ways of action. Artists in the role of teachers feel a responsibility both for the educational process and also for the emotional message that their creative product transmits to the audience.